Crowdfunding: A New Media & Society special issue. (February 2015) - Bennett, Lucy; Chin, Bertha; Jones, Bethan
As guest editors of this special issue of New Media & Society, we examine the concept of crowdfunding, where grassroots creative projects are funded by the masses through websites such as Kickstarter and Indiegogo, a practice that has been steadily gaining attention in the last few years, across many different sectors of society. We introduce the nine articles comprising the special issue and unravel the developments and challenges involved in these processes, concluding with suggestions for theoretical explorations and empirical considerations of the evolution and growth of crowdfunding within digital society.